2007
DOI: 10.1136/emj.2007.046904
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemic infarction masking aortic dissection: a pitfall to be avoided before thrombolysis

Abstract: Acute aortic dissection complicated by stroke is not uncommon but may be difficult to evaluate, especially in patients with impaired mental status. We report a patient who had evidence of an ischaemic stroke but was fortuitously not given thrombolytic treatment. She was subsequently found to have an extensive aortic dissection involving both carotid arteries. The decision of whether to give thrombolytic treatment is understandably an urgent one, but careful attention should be paid to subtle signs and symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…1,2 Data from randomized controlled trials on IVT in IS due to spontaneous artery dissection (AD) are not available. 6,7 Data on IVT versus placebo or versus any other antithrombotic treatment in patients with spontaneous AD are not available. Therefore, patients with spontaneous AD have not been specifically excluded from the randomized controlled trials of IVT in stroke.…”
mentioning
confidence: 99%
“…1,2 Data from randomized controlled trials on IVT in IS due to spontaneous artery dissection (AD) are not available. 6,7 Data on IVT versus placebo or versus any other antithrombotic treatment in patients with spontaneous AD are not available. Therefore, patients with spontaneous AD have not been specifically excluded from the randomized controlled trials of IVT in stroke.…”
mentioning
confidence: 99%
“…Yeh et al reported a case of a 56-year-old woman with vague chest pain and focal neurologic deficits whose decreased mental status on initial presentation made it difficult for a thorough medical history to be obtained. Diagnosis relied on CT angiography which delineated a type A AD involving both CCAs [4]. Similarly, Demiryoguran et al [5] reported a 63-year-old female with a predominant symptom of vertigo who was also found to have AD involving the ascending aorta, aortic arch, and bilateral common carotid arteries.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of these patients after rt-PA treatment was poor, with a reported mortality of up to 71%. 3 A literature review of the stroke field revealed three cases treated with thrombolysis, 1 , 4 , 5 and seven cases given only a loading dose or considered but not treated, 6 - 12 as summarized in Table 1 ; the mortality rates were 75% and 43% in the former and latter cases, respectively. Among the treated patients, one death was attributed to cardiac tamponade and intrapleural hemorrhage considered to be related to thrombolysis.…”
Section: Discussionmentioning
confidence: 99%